2017
DOI: 10.1108/jpbm-07-2016-1257
|View full text |Cite
|
Sign up to set email alerts
|

Consumer evaluations of trend imitation: brand equity, consumer attitudes and preference

Abstract: Purpose This paper aims to uncover consumer evaluations of high-priced traditional retail luxury brands and more affordable neo-mass luxury retail brands when they imitate the innovative designs of one another. Design/methodology/approach Using a scenario inspired by a lawsuit involving admitted copying practices, this study used a one-way (time of product introduction: the traditional luxury brand launches the product design before the neo-mass luxury brand vs the neo-mass luxury brand launches the product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…We assumed the presence of environmental concern and pro-environmental beliefs as antecedents for attitude and perceived consumer effectiveness. However, recent research found that consumers purchase sustainable goods also for reasons of reinforcing themselves, to signal uniqueness and due to a sense of empowerment through avoiding status or mass-produced goods (Bly et al, 2015;Dopico and Porral, 2012;Ferraro et al, 2016;Vogel and Watchravesringkan, 2017). As these factors are already known to be powerful players in fashion consumption, they should be incorporated when investigating sustainable consumer behaviour in the fashion context as well.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed the presence of environmental concern and pro-environmental beliefs as antecedents for attitude and perceived consumer effectiveness. However, recent research found that consumers purchase sustainable goods also for reasons of reinforcing themselves, to signal uniqueness and due to a sense of empowerment through avoiding status or mass-produced goods (Bly et al, 2015;Dopico and Porral, 2012;Ferraro et al, 2016;Vogel and Watchravesringkan, 2017). As these factors are already known to be powerful players in fashion consumption, they should be incorporated when investigating sustainable consumer behaviour in the fashion context as well.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, companies consider customer loyalty as the main source of competitive advantage. As a result, many minimarkets use loyalty programs to improve business, maintain and improve their relationships with customers [15].…”
Section: Customer Loyaltymentioning
confidence: 99%
“…For instance, Godey et al (2016) divided CBBE in brand awareness and brand image. Chahal and Rani (2017) considered brand awareness, brand image and brand loyalty as the dimensions of brand equity; Sasmita and Norazah Mohd Suki (2015) used brand awareness, brand loyalty, perceived quality of brand and brand association; GuzmĂĄn and Davis (2017) employed brand awareness, brand quality, and brand loyalty; and Vogel and Watchravesringkan (2017) reviewed brand associations, brand image, perceived quality and brand credibility. Among the different approaches, most researchers highlighted that CBBE combines two main components, namely, brand awareness and brand loyalty (Poulis et al, 2018).…”
Section: Customer-based Brand Equity (Cbbe)mentioning
confidence: 99%